Piezoelectric Output Analysis - Oktarina, Yurni; Nur Aina Okta Ferrisa; Pola Risma (Control and Computational Intelligent System (CoCIS) Research Group, 2024)
This study explores the utilization of mechanical energy generated from human footsteps as an alternative energy source through energy harvesting technology using piezoelectric materials. The designed system takes the form of a ceramic tile floor composed of four tiles arranged longitudinally, with each tile containing 30 piezoelectric elements, each 35 mm in diameter. The configuration consists of six piezoelectric units connected in series and five rows arranged in parallel, resulting in a total of 120 piezoelectric units in the entire system. The voltage, current, and power output depend on variations in body weight (60–94 kg), foot size, and the anatomical shape of the user's foot, which affect how many piezoelectric elements receive sufficient pressure during each step. The generated electrical energy is stored in a 12 Volt, 12 Ah battery for subsequent power use. Experimental results show that the system can produce varying amounts of energy depending on user physical parameters, indicating its potential for small-scale implementation in renewable energy applications within urban environments.